Transformative changes in cities: experiences of urban horticulture in Bariloche (Río Negro, Argentina) - Mattioli, Denise (2023)
In order to generate contributions to the field of urban-territorial studies and taking as a reference the context of the current climate crisis we outline a conceptual proposal about socio-ecological transitions around socio-food systems based on urban horticulture experiences. Based on an ethnographic case study in the town of Bariloche (Río Negro, Argentina), this research investigates social, economic and spatial aspects that emerge from family, community, intercultural, commercial and educational gardening experiences. This phenomenon has the particularity of developing in a city crossed by real estate speculation, the commodification of nature and socio-spatial inequality. The main findings are related to the emergence of a series of citizen networks and articulations to face the extended reproduction of life. It is considered that this type of agency can be read in terms of transformative changes, as they establish new approaches to the society-nature link from narratives on the commons, the collective and the right to the city.